Selection and evaluation of environmentally friendly pesticides, biological preparations and resistant varieties against harmful objects of melons and gourds in the conditions of the South-East of Kazakhstan (Eurasian Journal of Ecology, 2022)
In the Republic of Kazakhstan, melons are produced mainly by the traditional method, that is, by using chemical fertilizers and pesticides. The production of environmentally friendly melons is at the initial stage of its development. There is no organic melon growing at all. Considering the huge export potential of melons among other crops cultivated in the country (the total supply of melons and melons on the domestic market is 472%), the great economic and social importance of the direction of melons and gourds to organic production is growing. In the future, Kazakhstan may be in the center of attention of the world community as a producer and supplier of environmentally friendly (organic) melons, and environmentally friendly, natural melons may well become a brand of our sovereign state. To do this, it is necessary to make fundamental changes in the melon industry of the country.In general, the direction of agricultural products to organic production will contribute to the use of the safest and most useful products by the local population. Here, one should also take into account the decrease in the immunity of the human body due to various diseases, including those associated with the coronavirus pandemic.It should also be taken into account that only a limited number of pesticides used against harmful objects in agriculture act as intended, and the main part of toxic substances is distributed into the envi-ronment. The use of disinfectants without scientific support has a negative impact on flora and fauna, be-ing deposited on the soil and in the irrigation system of fields for a long time, thereby causing enormous damage to the environment.Considering the above facts, our scientific research was aimed at the selection of pesticides and biological preparations with high biological and economic efficiency, low rates and frequency of treat-ments, as well as varieties with high resistance to fungal diseases of gourds (watermelon, melon).Research work was carried out on the experimental plots of the Regional Branch «Kainar» of the LLP «Kazakh Research Institute of Horticulture» in the period 2020-2021. In the studies, classical methods generally accepted in melon growing were used. The results obtained are new and relevant, and in the future they will contribute to the transition from traditional melon growing to the biological direction. Key words: gourds, pesticides, biological preparations, pests, fungal diseases, tolerant varieties.